1962
DOI: 10.1149/1.2425233
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescent Lines in ZnS Powder Particles

Abstract: Several new embedding media of the same refractive index as ZnS are described which make possible the microscopic examination of the interior of electroluminescent particles taken from efficient industrial lots. Light is emitted in form of lines or striations extending through most of the diameter of the particles. The brightness of single lines has been measured in dependence of applied voltage, frequency, phase, and position along the line. Evidence is presented that the EL lines are associated with invisibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(60 citation statements)
references
References 13 publications
3
56
0
1
Order By: Relevance
“…The EL spectrum associated with these spikes (not shown here) is very similar to the regular EL spectrum of PPV. These observations are similar to the so-called out-of-phase EL spikes observed in the blue EL emitted by ZnS:Mn thin-film devices [89] and in ZnS:Cu powder phosphors dispersed in dielectric.…”
Section: Switching In Thicker Filmssupporting
confidence: 81%
“…The EL spectrum associated with these spikes (not shown here) is very similar to the regular EL spectrum of PPV. These observations are similar to the so-called out-of-phase EL spikes observed in the blue EL emitted by ZnS:Mn thin-film devices [89] and in ZnS:Cu powder phosphors dispersed in dielectric.…”
Section: Switching In Thicker Filmssupporting
confidence: 81%
“…On the basis of the previous studies [12,13] and results shown above, EL has been attributed to the ionization of activators by the impact of charge carriers accelerated by the high electric fields between Cu x S precipitates and ZnS:Cu,Cl matrix. It is believed that both the amount as well as the physical properties of Cu x S precipitates would influence the recombination rate and the following EL intensity.…”
Section: Resultsmentioning
confidence: 85%
“…According to the bipolar field emission model proposed by Fischer [12,13], conductive impurities such as cuprous sulfides (Cu x S) are necessary for luminescent ZnS particles to intensify the electric field, and to allow holes and electrons to recombine with radiation in luminescent centers. Therefore, by referring to the XRD analysis shown above, we can also predict that the samples fired at 900 • C with Cu Figure 3 shows the EL emission spectra of ZnS:Cu,Cl powders with various amount of Cu addition.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of high-field EL was proposed to result from the intensification of the electric field near a ZnS-Cu x S contact, and the induction of the tunneling charge carriers to activate the luminescence centers, e.g. Cu, Mn [2,3]. The precipitated Cu x S phase, which has been observed by Ono et al [4] and our group [5] by electron microscopy and optical analysis, is crucial to EL emission.…”
Section: Introductionmentioning
confidence: 68%